2016
DOI: 10.1155/2016/1576360
|View full text |Cite
|
Sign up to set email alerts
|

Pure Oats as Part of the Canadian Gluten-Free Diet in Celiac Disease: The Need to Revisit the Issue

Abstract: The question about recommending pure, noncontaminated oats as part of the gluten-free diet of patients with celiac disease remains controversial. This might be due to gluten cross contamination and to the possible immunogenicity of some oat cultivars. In view of this controversy, a review of the scientific literature was conducted to highlight the latest findings published between 2008 and 2014 to examine the current knowledge on oats safety and celiac disease in Europe and North America. Results showed that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
0
8
0
5
Order By: Relevance
“…Pure oats suitable for the gluten-free diet are grown, milled and handled without contamination by other cereals. Recently, it was suggested that the current confounding clinical findings on the safety of oat consumption in CeD subjects [32] could be caused by contaminated oats assessed as "pure" [8]. Indeed, a decade ago, gluten cross-contamination was shown to exist in oat supply chains in Europe, the United States and Canada [33].…”
Section: Discussionmentioning
confidence: 99%
“…Pure oats suitable for the gluten-free diet are grown, milled and handled without contamination by other cereals. Recently, it was suggested that the current confounding clinical findings on the safety of oat consumption in CeD subjects [32] could be caused by contaminated oats assessed as "pure" [8]. Indeed, a decade ago, gluten cross-contamination was shown to exist in oat supply chains in Europe, the United States and Canada [33].…”
Section: Discussionmentioning
confidence: 99%
“…Trata-se, portanto, de tema ainda controverso na literatura. 31,33,40,44,47,48 Quanto à SNCG/T, é incomum a referência à aveia, mas há assinalada ênfase no glúten do trigo como o principal, e talvez único, fator alimentar por trás desta condição. 11,49 Prevalência Uma porcentagem significativa da população geral relata problemas causados por ingestão de trigo e/ou de glúten, mesmo tendo sido devidamente excluídos os diagnósticos de DC e de AT.…”
Section: O Glútenunclassified
“…32 Trabalhos científicos recentes que tratam das doenças relacionadas ao glúten-especialmente a DC-e a Celiac Disease Foundation não incluem aveia entre os alimentos proscritos. 35,36 O risco, porém, de se consumir aveia, se dá pela contaminação por outros grãos, segundo vários autores, [37][38][39][40] o que ajuda a explicar a hesitação em liberar a ingestão de aveia para pacientes com DC. 41 Por outro lado, outros pesquisadores advertem que alguns cultivares de aveia podem exibir imunogenicidade relevante na patogênese da DC.…”
Section: O Glútenunclassified
“…Trata-se, portanto, de tema ainda controverso na literatura. 31,33,40,44,47,48 Quanto à SNCG/T, é incomum a referência à aveia, mas há assinalada ênfase no glúten do trigo como o principal, e talvez único, fator alimentar por trás desta condição. 11,49 Prevalência sistêmica em conjunto com um epitélio intestinal comprometido.…”
Section: O Glútenunclassified